2005
DOI: 10.1037/0022-3514.88.3.532
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Emotions and Helping: The Moderating Role of Group Membership.

Abstract: In this article, the authors introduce and test a group-level perspective on the role of empathy and interpersonal attraction in helping. In line with our predictions, Study 1, a longitudinal field study of 166 AIDS volunteers, confirmed that empathy was a stronger predictor of helping when the recipient of assistance was an in-group member than when that person was an out-group member. Also as hypothesized, attraction was a stronger predictor of helping when the recipient was an out-group member than when tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
278
1
12

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(316 citation statements)
references
References 48 publications
25
278
1
12
Order By: Relevance
“…Other recent research suggests that empathy can be shaped by group membership (who is in one's ingroup and outgroup; e.g. Stürmer, Snyder & Omoto, 2005; also Thomas et al, 2009). For example, Stürmer et al (2005) found that empathy was a stronger predictor of AIDS volunteerism for homosexual people (for whom the client was an ingroup member) than it was for heterosexual people (Study 1); and that empathy was a stronger predictor of spontaneous assistance for a person with hepatitis when that person was a (heterosexual) ingroup member than if they were an outgroup member (Study 2).…”
Section: Affective Antecedents Of Prejudice: the Role Of Empathymentioning
confidence: 99%
“…Other recent research suggests that empathy can be shaped by group membership (who is in one's ingroup and outgroup; e.g. Stürmer, Snyder & Omoto, 2005; also Thomas et al, 2009). For example, Stürmer et al (2005) found that empathy was a stronger predictor of AIDS volunteerism for homosexual people (for whom the client was an ingroup member) than it was for heterosexual people (Study 1); and that empathy was a stronger predictor of spontaneous assistance for a person with hepatitis when that person was a (heterosexual) ingroup member than if they were an outgroup member (Study 2).…”
Section: Affective Antecedents Of Prejudice: the Role Of Empathymentioning
confidence: 99%
“…O processo de projeção social faz com que as pessoas apresentem a tendên-cia de superestimar o compartilhamento de valores e ideias dentro de seu próprio grupo, construindo a percepção de uma identidade comum, e de subestimar as suas semelhanças com alguém de um grupo externo, devido à percepção de que entre os grupos existiria uma maior distância social (Robbins & Krueger, 2005). Alguns estudos têm apontado que existe um favoritismo dos membros do endogrupo em prestar ajuda mais frequentemente a membros categorizados de seu grupo do que para membros do exogrupo (M. Levine, Prosser, Evans & Reicher, 2005;Stürmer & Snyder, 2010;Stürmer, Snyder, Krop & Siem, 2006;Stürmer, Snyder & Omoto, 2005). Em geral, essas pesquisas têm sido feitas em ambientes laboratoriais e não foram identificados estudos brasileiros que apresentassem relatos do efeito que a categorização social tem sobre situações urbanas corriqueiras de ajuda.…”
Section: Os Autores Agradecem Aline Spezia Silva Maíra Guimarães Camposunclassified
“…Participants in this study may have been more or less inclined to help based on their own gender, as well as the gender of the pencil dropper. For example, Stürmer, Snyder, and Omoto (2005) found that volunteers helping in group members were more affected by empathy, but volunteers helping out group members were impacted by interpersonal attraction. Additionally, Bilewicz (2009) found that a person may be likely to help a member of the out group if he or she takes on the perspective of that person.…”
Section: Limitations and Future Researchmentioning
confidence: 99%